Treatment of periodontitis in smokers with multiple sessions of antimicrobial photodynamic therapy or systemic antibiotics: A randomized clinical trial - Theodoro, Letícia Helena [UNESP]; Assem, Naida Zanini [UNESP]; Longo, Mariéllen [UNESP]; Alves, Márcio Luiz Ferro [UNESP]; Duque, Cristiane [UNESP]; Stipp, Rafael Nobrega; Vizoto, Natália Leal; Garcia, Valdir Gouveia [UNESP] (Elsevier, 2018)
Background: The aim of this study was to evaluate the effects of non-surgical periodontal therapies on smokers with chronic periodontitis, involving multiple adjunctive applications of antimicrobial photodynamic therapy (aPDT), and systemic metronidazole (MTZ) with amoxicillin (AMX). Methods: All participants were treated with scaling and root planing (SRP). Seventeen patients received 400 mg of MTZ and 500 mg of AMX three times per day for 7 days (MTZ + AMX). Additionally, 17 patients received a placebo, and 17 patients were treated with three applications of aPDT (immediately, 48 h and 96 h after SRP). Clinical and microbiological examinations were performed at baseline and at 90 and 180 days post-therapy. Subgingival samples were analyzed using real-time polymerase chain reaction. Results: After 180 days, the patients in groups MTZ + AMX and aPDT had significantly lower mean probing depths, more clinical attachment level gains and less bleeding on probing. At 180 days, in the moderate pocket there was a reduction in the levels of Porphyromonas gingivalis and Prevotella nigrescens in the MTZ + AMX group, while group aPDT showed a reduction in Prevotella nigrescens. Furthermore, at 180 days, in the deep pocket a reduction in Porphyromonas gingivalis, Prevotella intermedia and Prevotella nigrescens was observed in group MTZ + AMX, as well as a reduction in the levels of Prevotella intermedia and Prevotella nigrescens in group aPDT. Conclusion: In smokers with periodontitis, the MTZ + AMX and aPDT treatments significantly improved the effects of SRP.
Keywords: Antibiotics; Periodontitis; Photochemotherapy; Photodynamic Therapy; Smoking